Development of Real-Time Air Quality Monitoring Device with Graphical User Interface (GUI) - Zaherman, Siti Zaimah Atiqah; Mohd Arif Rosli; Amirul Syafiq Sadun (Progress in Engineering Application and Technology, 2024)
Air is one of the most significant elements of the environment humans live in. Rapid industrialization, urbanization, and commercial activity are harming the once-beautiful natural environment. The "digital revolution" is bringing significant changes to building design concepts, transforming design culture, and increasing the demand for a renewed link between technology and the environment. The biggest, heaviest, and most costly characteristics of conventional monitoring equipment, such as the E-Sampler tool, are their disadvantages. This study aims to develop a real-time air quality monitoring device with a Graphical User Interface (GUI) to monitor ambient air quality and test its functionality in an indoor location at UTHM Pagoh. The new device will upload data to a database accessible via LabVIEW software, incorporating ten characteristics: humidity, temperature, light intensity, air pressure, carbon dioxide, carbon monoxide, alcohol, acetone, ammonia, and toluene. Two tools will be used simultaneously for testing: the new device operating for 24 hours and the Delta Ohm Datalogger (HD37AB1347) operating for 7 hours. Testing will be conducted in two indoor laboratories: Blok A1 Kolej Kediaman Pelajar Universiti Tun Hussein Onn, Malaysia, and Makmal Pemasangan dan Pembuatan (Blok B), Bengkel Teknologi Konkrit (Blok F). The results and analysis will focus on the functionality of the new device by comparing data from the newly developed IoT device with traditional indoor air quality devices across different locations. The study will conclude with findings and recommendations for future improvements in air quality monitoring technology.